1998
DOI: 10.1038/bjc.1998.523
|View full text |Cite
|
Sign up to set email alerts
|

The Royal Marsden experience of small bowel adenocarcinoma treated with protracted venous infusion 5-fluorouracil

Abstract: Summary The purpose of this study was to review the efficacy of a protracted venous infusion of 5-fluorouracil (PVI 5-FU)-based chemotherapy in advanced small bowel adenocarcinoma. Data on all patients with small bowel malignancy who were seen at a single institution over a 5-year period were retrieved from the gastrointestinal unit and hospital databases, and these cases were reviewed. Eight patients with advanced small bowel adenocarcinoma received PVI 5FU-based chemotherapy. The overall response rate in ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 12 publications
0
47
0
1
Order By: Relevance
“…Fluoropyrimidines are generally considered to be the key drugs for SBA and other gastrointestinal cancers. Most regimens used in previously reported studies of chemotherapy for unresectable SBA included fluoropyrimidines; to date, there has been no active regimen without these drugs [11][12][13][14][15][16][17][18][19][20][21][22][23]. However, no prospective or retrospective study has clearly showed advantages of a combination regimen compared with fluoropyrimidine monotherapy for unresectable SBA with regard to PFS or OS times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoropyrimidines are generally considered to be the key drugs for SBA and other gastrointestinal cancers. Most regimens used in previously reported studies of chemotherapy for unresectable SBA included fluoropyrimidines; to date, there has been no active regimen without these drugs [11][12][13][14][15][16][17][18][19][20][21][22][23]. However, no prospective or retrospective study has clearly showed advantages of a combination regimen compared with fluoropyrimidine monotherapy for unresectable SBA with regard to PFS or OS times.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorouracil (5-FU) is the most commonly used agent for the treatment of unresectable or recurrent SBA, and various 5-FU based regimens have been used [11][12][13][14][15][16][17][18][19][20][21][22][23]. In a retrospective analysis, Overman et al reported that combination therapy with 5-FU and platinum compounds showed more favorable results than other regimens [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although most experience is with colorectal, gastric, and esophageal cancers, additional reports of treatments for advanced small bowel adenocarcinoma do exist. Crowley et al [11] reported the Royal Marsden experience of using infusional 5-FU as a single agent or in combination with cisplatin and epirubicin (Ellence ® ; Pharmacia and Upjohn; Portage, MI), the ECF regimen [10]. Of the eight patients assessable for response, one achieved a CR and two achieved PRs (RR = 37%), with a median overall survival time of 13 months.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for SBA, including Crohn’s disease, celiac sprue, familial adenomatous polyposis, hereditary nonpolyposis colorectal cancer syndrome, Peutz-Jeghers syndrome, and type 1 neurofibromatosis, account for a minority of cases [2]. This mostly sporadic pattern of occurrence, along with the lack of specificity of clinical symptoms, largely explain why approximately one half of cases of SBA are not diagnosed prior to surgery, and why up to two thirds of cases are not amenable to curative resection at the time of diagnosis [1,3,4,5]. Patients with high-stage tumors remain at risk of recurrence even after complete resection [6], and the benefit of adjuvant therapy in such patients is still debated [6, 7].…”
Section: Introductionmentioning
confidence: 99%